Uji Coba Bahan Ajar Muatan Lokal Seni Rupa Tradisional Bengkulu Terhadap Hasil Belajar Siswa Kelas VA SD Negeri 49 Kota Bengkulu - Wanda Pratama; Hasnawati Hasnawati; Resnani Resnani (JURIDIKDAS, 2018)
Research aims to determine the difference learning outcomes VA grade students at SDN 49 Bengkulu City. This type of research is quantitative research, the research method used is Pre-Experimental Design with this type of design one group pretest-posttest design, sample in this study were students of SD Negeri 49 VA Bengkulu City. The research instrument used is a sheet in the form of a multiple choice test given by the pretest and posttest. Data from this study were analyzed using descriptive and inferential analysis that the t-test. The survey results revealed that the average value posttest (65.64) is higher than the average value of pretest (46.14). t-test results with ttabel 8.193 and thitung 1.720. So, ttabel (8.193) > thitung (1,720). thitung value obtained is higher than the value ttable it can be concluded that the difference between the results of student learning so that there are effects of the application of local content teaching materials of traditional art Bengkulu on learning outcomes VA grade students at SD Negeri 49 Bengkulu City.